The spaces in between: an actor network analysis of alternative food systems in Latin America and the Caribbean - Lizarralde, Gonzalo; Latorre, Sara; Clavijo, Neidy; Herazo, Benjamin; Pérez, Manuel; Gould, Kevin; Paredes, Myriam; Monsalve, Elsa; Ordoñez, Nicolas; Burdiles, Roberto; Araneda, Claudio; Bornstein, Lisa; et al. (Frontiers in Sustainable Food Systems, 2025)
For years, researchers and activists have claimed that alternative food systems are required to increase the resilience of low-income families in the Global South and overcome the negative effects of capitalist, agro-industry regimes. Urban and peri-urban agriculture and alternative forms of local food production and distribution in urban settings are often seen as promising strategies. Yet very little is still known about how local food initiatives emerge, are legitimized, and (sometimes) survive in contexts of informality. Here we use Michel Callon’s conceptual tools to reveal how alternative food networks are justified and operate in low-income settlements where informal construction and economic activities abound. We conducted 340 interviews and 312 questionnaires and followed 18 bottom-up initiatives related to food production, distribution, transformation and consumption in cities and peri-urban spaces in Colombia, Cuba, Ecuador, and Chile. Empirical results show how, seeking to stabilize food systems, local leaders create design outcomes and activities where social struggles, identities, and reified notions of time and space are key. From a practical perspective, these results show the inadequacy of regulations and policy to grasp the dynamic resistance occurring in the “in between” spaces of both identities and urban structure. Changes in urban policy and food programs are required to make sense of such complexity.